2006
DOI: 10.1016/j.cardiores.2005.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Reduced arteriolar conducted vasoconstriction in septic mouse cremaster muscle is mediated by nNOS-derived NO

Abstract: Increased nNOS activity and the resultant increased NO production in the septic mouse cremaster muscle are the key factors responsible for the deficit in conducted vasoconstriction along the arteriole. Deletion of Cx37 results in reduced CR500, which is consistent with the hypothesis that Cx37 in the arteriole could be a target of NO signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
58
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 39 publications
4
58
2
Order By: Relevance
“…The role of Cx37 in the vasculature has previously been analyzed in mice deficient for Cx37, which showed impaired conduction of arteriolar vasoconstriction (19) and susceptibility to atherogenesis (35). Colocalization of Cx37 with renin suggests a role for Cx37 in renin release, although Cx40 Ϫ/Ϫ rather than Cx37 Ϫ/Ϫ mice showed an obvious renin-related phenotype with increased circulating renin levels and hypertension (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of Cx37 in the vasculature has previously been analyzed in mice deficient for Cx37, which showed impaired conduction of arteriolar vasoconstriction (19) and susceptibility to atherogenesis (35). Colocalization of Cx37 with renin suggests a role for Cx37 in renin release, although Cx40 Ϫ/Ϫ rather than Cx37 Ϫ/Ϫ mice showed an obvious renin-related phenotype with increased circulating renin levels and hypertension (14).…”
Section: Discussionmentioning
confidence: 99%
“…It displayed a high homology with other Cx in its extracellular domains, whereas little or no homology was found in the cytoplasmic loop connecting the second and third hydrophobic region and the COOH-terminal chain. Modulations of Cx37 occurred via posttranslational modifications including phosphorylation and probably nitrosylation (19). Functionally Cx37 has been shown to form intercellular channels that exhibit specific channel properties such as voltage gating (34).…”
mentioning
confidence: 99%
“…However, under pathophysiological conditions with supposedly even higher NO levels a further attenuation seems to be possible, since treatment with LPS (33,34) or induction of sepsis attenuated the conduction process in vivo without prior inhibition of endogenous NO release (22,34). These authors demonstrated that the effect of LPS was mediated by NO and have identified neuronal NO synthase as the source of NO under these conditions (26). Nevertheless, these observations are in good agreement with the data presented in this report, and the present study extends these findings by demonstrating a role for the basal NO release from eNOS and thus expanding the regulatory role for NO toward physiological conditions.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, it is rather unclear which connexin is targeted by such a regulatory mechanisms in vivo. Initially, Cx43 was proposed as a target (23), and later Cx37 (26) and Cx40 during study of hypoxia/ reoxygenation (4). Therefore, we hypothesized that endogenous NO acts as a regulatory factor on GJIC in vivo in a cGMP-dependent fashion.…”
mentioning
confidence: 98%
See 1 more Smart Citation